The Influence of Capital Structure, Company Size, and Financial Performance on the Company's Value (An Empirical Study on Companies in Various Industrial Sub-Sectors Listed on the Indonesia Stock Exchange (IDX) in 2021–2023) - Nur Atikah; Retno Kurnianingsih (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The purpose of this study is to analyze the influence of capital structure, company size, and financial performance on the company's value. The research uses a quantitative approach. The data used is secondary data obtained through the IDX's official website, namely www.idx.co.id, in the form of company financial statements in various industry subsectors during 2021–2023. Of the 67 companies that became the population, as many as 25 companies were selected as samples using the purposive sampling method based on certain criteria. The results of the analysis show that the company's capital structure and size have a positive and significant impact on the company's value, while financial performance has a negative and significant impact on the company's value.